The contributions of grandparents to preadolescent grandchildren's social skills in rural Malaysia - Jo-Pei Tan; Su-Wan Gan; Charissa S. L. Cheah; Soon-Aun Tan; Sarvarubini Nainee; Chin Choo Yap; Kai Yee Hon (ResearchGate, 2024)
This study aimed to generate localized knowledge by investigating the perceptions and experiences of preadolescent grandchildren and grandparents regarding grandparenting and intergenerational interactions and how these processes were related to the social skills of preadolescents from three ethnic groups in Malaysia. Using a concurrent quantitative–qualitative mixed method research design, Chinese, Malay, and Indian preadolescents (N=465; ages 9–12 years old; M=10.27 years; SD=1.03) from rural areas in Malaysia completed a self-administered quantitative survey; furthermore, 25 grandparents participated in one-on-one interviews. Survey findings showed that preadolescent grandchildren who reported higher grandparental warmth and support had greater social skills, mediated by positive grandparent–grandchildren (GP–GC) relationships. The GP–GC relationship and preadolescent social skills association was stronger for skipped generation compared to three-generation households. Interview findings revealed that grandparents expressed unconditional love and autonomy support in their grandparenting roles by guiding and encouraging their preadolescent grandchildren to make decisions. The GP–GC interactions served as a dynamic force in promoting preadolescents' social skills. By employing a decolonized approach and drawing on the lived experiences of grandparents from three ethnic backgrounds in rural Malaysia, the study provided an understanding of grandparenting practices and their general implications across the three ethnic groups. The interview responses highlighted both commonalities and specificities in grandparenting practices and relationship dynamics shaped by religious, class, and sociocultural dimensions in rural Malaysia.